2020
DOI: 10.1002/ppp3.10097
|View full text |Cite
|
Sign up to set email alerts
|

Banishing the myths and dogmas surrounding the biotech Stradivarius

Abstract: Societal Impact Statement The impact of global warming on wood formation means that it is becoming increasingly difficult to find superior‐quality resonance wood for the production of musical instruments. Using fungi, we can mimic the effects of a cold climate on wood, to produce biotech violins with a tone matching those of a Stradivarius. Our work has sparked worldwide interest from the media, music lovers, and violinmakers. Here we address concerns raised about the biotech violin and detail scientific advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…During this period, Stainer created his own style, producing exceptional instruments that rivaled or even surpassed the works of his Cremonese contemporaries of the seventeenth century. As specific constructive features, we can notice that the arching of the front plates is higher than that of the rear plates; the growth is maintained up to half the length; and the finish used is yellow, with a shade of pale rose [4][5][6]. The resonant bar is terminated at its two ends by bevels that extend on the sound plate to which it is glued, being placed under the G string of the instrument.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, Stainer created his own style, producing exceptional instruments that rivaled or even surpassed the works of his Cremonese contemporaries of the seventeenth century. As specific constructive features, we can notice that the arching of the front plates is higher than that of the rear plates; the growth is maintained up to half the length; and the finish used is yellow, with a shade of pale rose [4][5][6]. The resonant bar is terminated at its two ends by bevels that extend on the sound plate to which it is glued, being placed under the G string of the instrument.…”
Section: Introductionmentioning
confidence: 99%
“…Babos Bela was a representative of the Hungarian violin school from the beginning of the 20th century [5,6]. In Romania, in the well-known city of violins, Reghin, the art of violin making developed to a level of qualitative and aesthetic perfection, with numerous violin workshops, due to the high quality of wood existing in the area known in antiquity as the Italian valley.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21]. Many of these musical ins are rare examples of high artistic mastery and are still used as referenc contemporary manufacture of violins [22][23][24]. From this aspect, the determinin have been analyzed over time: the structural quality of wood, moisture conte aging, plate geometry (thickness/arching), finishes used, constructive elemen post, position and shape of acoustic holes, sounding bar, bridge), and string qual studies have highlighted the effect of aging wood and varnish, the contributi primer and even the attack of fungi on the acoustic quality of old violins [25-28 conducted over time on old and new violins show contradictory results: in som the acoustic and dynamic response of old violins is presented as a standard for th of new ones; in other studies in which the acoustic impressions of soloists were through blind tests (without the respondents seeing the violins or knowing thei the results showed that, from the point of view of the acoustic criteria, the ne present a much more appreciated acoustic quality than the old ones [24,29 Regarding old violins, built by well-known luthiers such as Stradivarius, Guarnieri, Amatti, Stainer, Klot and Leeb, there are numerous studies on the structure of wood, its anatomical quality, wood dating, types of varnish used, structural integrity using modern techniques modern, ways of restoration, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21]. Many of these musical instruments are rare examples of high artistic mastery and are still used as references in the contemporary manufacture of violins [22][23][24]. From this aspect, the determining factors have been analyzed over time: the structural quality of wood, moisture content, wood aging, plate geometry (thickness/arching), finishes used, constructive elements (sound post, position and shape of acoustic holes, sounding bar, bridge), and string quality.…”
Section: Introductionmentioning
confidence: 99%
“…Wood decomposing fungi also harbour huge potential for novel applications, such as in the development of fungal-induced bow instruments (i.e. the 'biotech Stradivarius'; [65]) and wood products with artistic appeal. Visible indicators of wood decay such as zone lines (also known as demarcation lines) and wood discoloration induced by fungi are collectively referred to as spalting or spalted wood [58].…”
Section: Introductionmentioning
confidence: 99%